ANALISIS REALISASI PUNGUTAN BEA MASUK DAN PAJAK DALAM RANGKA IMPOR DIMASA PANDEMI COVID-19 PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN A MARUNDA - saprudin; Deby Dahlin Abdurozak; Rudy Hedianton Saragih (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2023)
A fiscal policy package for economic stimulus has been issued to reduce the impact of the pandemic on the economic sector. The results of this study will later explain that the collection of import duties and taxes in the framework of imports greatly influences the total state revenue. Therefore, this research is expected to be able to provide input to the Customs and Excise Service Office of Customs Type A Marunda to be able to maximize the performance of existing importers so that the import of goods does not use the import duty exemption tariff and increase socialization to service users (importers) to boosting the level of compliance in reporting data on imports of goods correctly so that it can increase the total revenue of the Customs and Excise Service Office of Customs and Excise Type A Marunda in the future